KELAYAKAN MEDIA FLIPCHART PADA SUB MATERI TUMBUHAN PAKU KELAS X SMA DI MANDOR - Lestari, Maya Anggraini; Syamswisna, Syamswisna; Yokhebed, Yokhebed (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
ABSTRACTThe aim of present study was to measure the feasibility of flipchart media on ferns sub-topic. The method used in this research was descriptive method with quantitative research technique. This flipchart media then was tested for feasibility by media experts. Flipchart media was validated by two lecturers of Biology Education of FKIP Untan and three biology teachers of class X three senior high schools in Mandor District. According to the validators, , the flipchart was valid with the average score of the Content Validity Index (CVI) 0.93 and feasible to use as a learning media for ferns sub-topic (Pteridophyta).Keywords: Feasibility, Flipchart, Ferns sub-topic